1958
DOI: 10.1515/znb-1958-0505
|View full text |Cite
|
Sign up to set email alerts
|

Über die Verteilung von Radioyttrium und radioaktiven Seltenen Erden im Säugerorganismus

Abstract: Es wird über das Vertcilungsmuster von Radioyttrium (91Y) in Meerschweinchen nach intrakardialer, intraperitonealer und subkutaner Applikationsweise und die dabei auftretenden Unterschiede berichtet. Nach der Inkorporation von Yttrium muß mit einer Leberpassage vor der Knochenspeicherung gerechnet werden. Die hohen Aktivitäten in Leber und Nieren bedürfen mehr als bisher der strahlenbiologischen Beachtung

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1958
1958
1982
1982

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…All of the investigated lanthanons were strongly concentrated in the liver as early as one hour after intravenous administration. This confirms earlier investigations done on rats (Durbin et al 1956, Aeberhardt et al 1961 as well as mice (Laszlo et al 1952b, Rosoff et al 1963 and guinea pigs (Spode 1958, Graul & Hundeshagen 1959, Spode & Gensicke 1961. The fact that light lanthanons have a greater uptake by the liver is also in accordance with earlier experiences.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…All of the investigated lanthanons were strongly concentrated in the liver as early as one hour after intravenous administration. This confirms earlier investigations done on rats (Durbin et al 1956, Aeberhardt et al 1961 as well as mice (Laszlo et al 1952b, Rosoff et al 1963 and guinea pigs (Spode 1958, Graul & Hundeshagen 1959, Spode & Gensicke 1961. The fact that light lanthanons have a greater uptake by the liver is also in accordance with earlier experiences.…”
Section: Discussionsupporting
confidence: 91%
“…Durbin et al (1956) states a plasma concentration for cerium-144 and terbium-160 of the same amount as in the present investigation. In guinea pigs, the blood concentration falls somewhat more slowly than in rats with yttrium-91 (Spode 1958) as well as cerium-144 (Spode & Gensicke 1961). Aeberhardt et al (1962) found approximately the same blood concentration for ionized radioceriuni as has been shown in the present experiments.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…When incorporated in equilibrium with its daughter radionuclide yttrium-90, the two radionuclides take different metabolic pathways and show different tissue-affinities. While 90y goes through transient accumulation in the liver, spleen and other organs abundant in reticulo-endothelial tissues, 9°Sr is directly deposited in the mineral component of bone (Spode 1958;Steinbach 1966; see also Lloyd 1961). Owing to this metabolic behaviour, the haemopoietic system is subjected to non-uniform irradiation at least during the early phase of incorporation.…”
Section: Introductionmentioning
confidence: 99%